Patient’s Refusal of Early Treatment of a Cesarean Scar Pregnancy Resulting in Life - Saving Hysterectomy at 23 Weeks Gestation: Report of a Case - Çalışkan, Eray; Çakıroğlu, Yiğit; Çorakçı, Aydın (Gynecology Obstetrics & Reproductive Medicine, 2008)
Cesarean scar pregnancy (CSP) is a rare life-threatening form of ectopic pregnancy embedded in the myometrium of a previous cesarean scar. Pathogenesis is suggested to be related with an existing scar defect or a microscopic dehiscent tract generated between the prior cesarean scar and the endometrial canal. The most common risk factor is a history of previous cesarean section. Sonography is the firstline diagnostic tool for the diagnosis of CSP. It is possible to make the diagnosis in the early weeks of pregnancy and early diagnosis would let the patient retain her future fertility. Treatment options prior to rupture include expectant management, dilatation&curettage, conservative medical treatment, hysteroscopic- laparoscopic-primary open surgical removal or hysterectomy. We herein present a case of Cesarean scar ectopic pregnancy complicated with uterine rupture at 23 weeks’ gestation.